2017
DOI: 10.1108/h-06-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of household’s education and nutrition spending

Abstract: Purpose This study aims to estimate the determinants of household spending on education and nutrition. Education and nutrition are noteworthy elements for human development and welfare. Separate estimates are being provided for male and female as gender determines household welfare and gender-based analysis of household spending evaluates the aptitude of decision power as well as measures their influential role in human welfare. Design/methodology/approach Fruits, milk and dairy products are taken as proxy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…These results indicate that being literate has a positive contribution on women's nutrition security status. This finding is consistent with a report from Pakistan [29].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results indicate that being literate has a positive contribution on women's nutrition security status. This finding is consistent with a report from Pakistan [29].…”
Section: Discussionsupporting
confidence: 94%
“…Family size (adult equivalent) was reported to have a highly significantly negative effect on food security status in Afar Region of Ethiopia [27]. Kousar et al [29] reported that the number of employed household members, level of income, and education are positively associated with household spending on education and nutrition by male-and female-headed households; and Cherotich et al [30] reported a positive association between women's financial knowledge and the amount of savings and profit margins from their farm enterprises. This study was carried out to determine the factors (determinants) influencing the nutrition security status of rural women in Northwest Ethiopia by using a household survey data conducted in 2019 and analyzed using a binary Logit regression model.…”
mentioning
confidence: 99%
“…In a study conducted in China, it was found out that families with higher income, well-educated and professional parents made more education expenditure (Qian & Smyth, 2011). It was reported in another study executed in Pakistan that as household income increased, education expenditures raised, too (Kousar et al, 2017). In a study conducted in Turkey, it was established that as the total expenditures of low-income households increased, their education expenditures increased at a slower rate.…”
Section: Discussionmentioning
confidence: 98%
“…There is comprehensive literature showing that educational expenditures have significant effects on education (Acerenza & Gandelman, 2019;Andreou, 2012;Chi & Qian, 2016;Deng & Xue, 2014;Donkoh & Amikuzuno, 2011;Himaz, 2010;Huy, 2012;Jenkins et al, 2019;Kousar et al, 2017;Majumder & Mitra, 2016;Wei et al, 2021). There are a number of studies carried out regarding the educational expenditure of households in Turkey (Acar et al, 2016;Bayar & İlhan, 2016;Demiroglari 271 & Kiren Gurler, 2020;Kuvat & Ayvaz Kizilgol, 2020;San & Chaloupka, 2016;Susanli, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This study also observed that about 2 in every 3 female household heads were either widowed or divorced, a finding which corroborates the report that female household heads are more of the divorced and widowed population (Oginni et al, 2013;Milkalitsa, 2015). The high mortality rate among males has been identified as a factor attributed to the continual rise in females becoming household heads in developing countries of the world (Motts, 1994;Banerjee and Roy, 2015;Kousar et al, 2017). According to some reported studies, singlehood, separation/divorce and widowhood have been attributed to the shift in responsibilities to care for children which opens women and the wards to vulnerability (Chant, 2003;Opara, 2016).…”
Section: Discussionmentioning
confidence: 99%